Hubungan Sanitasi, Status Imunisasi dan Riwayat Pemberian Makan Prelakteal terhadap Kejadian Stunting pada Balita Usia 6-24 Bulan di Desa Simpang Rimba Tahun 2022 - Mutmainah, Laeli; Jatmiko, Suyana; Rinasari, Nania; Tayib, Yusri (Media of Health Research, 2024)
Stunting is a growth disorder condition caused by chronic long-term malnutrition. The aim of this study was to determine the relationship between immunization status, sanitation, and a history of prelacteal feeding with the incidence of stunting among children aged 6–24 months in Simpang Rimba Village in 2022. This research used a quantitative method with a cross-sectional study design. The study was conducted from August 2022 to January 2023. The study population consisted of mothers with children aged 6–24 months living in Simpang Rimba Village under the jurisdiction of Rias Community Health Center, South Bangka Regency, totaling 106 individuals. The sample size was 52 respondents. Data were analyzed using univariate and bivariate methods. Univariate analysis showed that 32.7% of respondents' children experienced stunting, 84.6% of respondents had children with complete immunization status, 53.8% practiced poor sanitation, and 51.9% had provided prelacteal feeding. Bivariate analysis revealed no significant relationship between immunization status and stunting (p = 1.000), a significant relationship between sanitation and stunting (p = 0.047), and a significant relationship between the history of prelacteal feeding and stunting (p = 0.030). The study concludes that sanitation and history of prelacteal feeding are the variables associated with stunting among children aged 6–24 months in Simpang Rimba Village. It is recommended that mothers pay greater attention to environmental sanitation and infant feeding practices.